Nursing Errors in Iranian Nurses: A Mixed Study - Monirsadat Nematollahi; Behnaz Bagherian; Roghayeh Mehdipour‐Rabori (Health Science Reports)
ABSTRACT Background and Aims Medical errors that result in patient injuries and fatalities are a significant concern in healthcare. Understanding these errors and their contributing factors is essential for enhancing the quality of patient care. This study aimed to investigate nursing errors and the factors that influence them. Methods This study employed a mixed‐method approach with a sequential explanatory design and was conducted in Iran from 2022 to 2023. The study consisted of two phases. In the quantitative phase, a cross‐sectional study was conducted in which 200 nurses in Kerman City completed two questionnaires: one on nursing errors and the other on factors influencing nursing errors. In the qualitative phase, the researchers conducted semi‐structured, in‐depth, face‐to‐face individual interviews with 30 nurses. Results Two hundred nurses took part in the quantitative phase, and 99% of them reported experiencing at least one nursing error. The highest average score for errors was associated with medication errors (3.40 ± 0.37), followed by care errors (2.85 ± 1.34). The average scores for the most prevalent causes of errors were highest in the organizational dimension (3.8 ± 1.01). A significant positive correlation was found between the average scores of various error dimensions and the average scores of different dimensions related to the causes of errors (p < 0.05). Three main categories were identified from the qualitative data: “Nursing errors must be reported,” “Doom of conscience after committing a nursing error,” and “Error in nursing is multifactorial.” Conclusion The study revealed a high prevalence of nursing errors, emphasizing the need for proactive measures. Healthcare system managers and decision‐makers must take into account the factors that contribute to nursing errors and respond appropriately to eliminate or reduce them.